2008
DOI: 10.1097/inf.0b013e3181598315
|View full text |Cite
|
Sign up to set email alerts
|

Foscarnet Salvage Therapy for Acyclovir-Resistant Varicella Zoster

Abstract: The authors describe an acyclovir-resistant varicella zoster virus infection in a pediatric patient after hematopoietic stem cell transplant, the use of foscarnet as salvage therapy, and review the literature to clarify the pediatric experience with foscarnet in this setting. A novel thymidine kinase mutation is described, along with a new phenotypic assay for characterizing acyclovir resistance in varicella zoster virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although acyclovir-resistant HZ has been described 32 , it is rare in HCT recipients 33,34 , and there was no clinical evidence for resistance in our patients who were taking ACV/VACV prophylaxis at the time of HZ based on subsequent response to these agents. VZV-specific T-cell reconstitution in allogeneic HCT recipients does not appear to be adversely affected by prolonged use of prophylactic ACV after HCT 14 , suggesting that the continued risk for HZ after discontinuation of antiviral prophylaxis likely reflects a prolonged immunodeficiency 9 .…”
Section: Discussionmentioning
confidence: 58%
“…Although acyclovir-resistant HZ has been described 32 , it is rare in HCT recipients 33,34 , and there was no clinical evidence for resistance in our patients who were taking ACV/VACV prophylaxis at the time of HZ based on subsequent response to these agents. VZV-specific T-cell reconstitution in allogeneic HCT recipients does not appear to be adversely affected by prolonged use of prophylactic ACV after HCT 14 , suggesting that the continued risk for HZ after discontinuation of antiviral prophylaxis likely reflects a prolonged immunodeficiency 9 .…”
Section: Discussionmentioning
confidence: 58%
“…However, ACV-resistant VZV is a problem for immunocompromised patients that may pose therapeutic dilemmas. 2 Foscarnet and cidofovir are therapeutic options in many of these cases, 3,4 and amenamevir is now another treatment option in Japan.…”
Section: Improvement Of Acyclovir-resistant Herpes Zoster Infection By Amenamevirmentioning
confidence: 99%
“…It is suggested that the occurrence of viral TK-associating ACVr mutations in VZV is much less frequent than in HSV-1. ACVr VZV is reported rarely in immunocompromised patients (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In contrast, ACVr HSV-1 occurs in 3.5% to 10% of immunocompromised patients (2,(24)(25)(26)(27)(28).…”
mentioning
confidence: 98%